IMPLEMENTASI PROGRAM DESA WISATA DI DESA SAWAHAN KECAMATAN WATULIMO KABUPATEN TRENGGALEK - Yolanda Azhari; Tjitjik Rahaju; Indah Prabawati; Ahmad Nizar Hilmi (Universitas Negeri Surabaya, 2026)
Tourism plays a crucial role in economic development and improving community welfare, with management currently focused on the Community-Based Tourism (CBT) approach. This concept encourages community empowerment through the development of tourism villages that integrate natural, man-made, and cultural potential in a participatory manner. Sawahan Village in Watulimo District, Trenggalek Regency, is one of the villages developing a tourism village program. However, its implementation still faces several obstacles. This study aims to describe the implementation of the Tourism Village Program in Sawahan Village. The method used is descriptive qualitative with a bottom-up policy implementation theory approach according to Elmore, Lipsky, O'Porter, and Hjern. The results show that program implementation involves a network of actors, namely the Trenggalek Regency Tourism and Culture Office, the village government, the Duren Sari Tourism Group (Pokdarwis), and the community. The bottom-up policy approach is reflected in the management of tourism packages and homestay businesses by the community as the primary implementer, while the village government acts as a supervisor and the agency as an advisor. Although the actors' roles have been quite successful, program evaluation has not been conducted in a structured and sustainable manner, and training from the agency has not been optimal. Community participation, especially among the younger generation, is also still limited. Therefore, regular evaluation, capacity building of managers, and innovation of tourist attractions are needed so that the benefits of the program are felt more evenly and sustainably.